Optimizing Tourism Supply Chain: Improving Service Quality and Tourist Loyalty - Nurita Andriani; Miftahul Jannah; Nurul Ilyana Muhd Adnan (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Tourism supply chains are essential in delivering services to consumers and supporting destination competitiveness. This study examines the effect of service quality of tourism supply chain on tourist satisfaction and loyalty. Using a quantitative design with purposive sampling, data were collected from 150 respondents aged 17 years and above who had traveled through a travel agency. The data were analyzed with Partial Least Squares–Structural Equation Modeling. The results show that service quality of tourism supply chain has a significant positive effect on both satisfaction and loyalty. However, satisfaction does not influence loyalty and does not mediate the relationship between service quality of tourism supply chain and loyalty. These findings indicate that service quality plays a more direct role in shaping tourist loyalty, while satisfaction alone may not ensure repeat visits. The study contributes to tourism supply chain research and suggests that destination managers should prioritize improving service quality integration to strengthen tourist loyalty.